(untitled) (Società e diritti, 2021)
Abstract The provisions of the ADR tools, such as mediation, contained in the legislation for health emergencies, appear partial with regard, above all, to their limitation in the period of validity of the state of crisis and their limited ultractivity over time. Therefore, it is not expected that they are suitable for producing their effects even beyond the emergency period, when it can be considered that they have only formally “exited” the crisis; but the negative effects in the contractual matter subject to ADR (such as, among all, the persistence of the difficulty in fulfilling one’s obligations), cannot be declared terminated at all. It is very likely that the difficulties will go far beyond that. This temporal limitation appears to be the result of a lack of programmatic attention by the legislator and a confirmed logical-legal distrust towards ADR instruments which, however and instead, even more in an exceptional period such as the present and well beyond, could express their broadest scope. and value for all controversial situations that arise, immediately and mediately, from the health emergency.